To flea or not to flea: survey of UK companion animal ectoparasiticide usage and activities affecting pathways to the environment - Perkins, Rosemary; Goulson, Dave (PeerJ, 2023)
Due to the convenience and efficacy of modern ectoparasiticides, routine prophylactic use has become commonplace for dogs and cats. However, the environmental consequences of this large-scale use are not well-understood, and multiple potential pathways for ectoparasiticides to the environment exist. Of particular concern is the potential for topically applied ectoparasiticides to pass to waterways, both down-the-drain via wastewater treatment plants and directly through swimming. In this online cross-sectional survey of 1,009 UK cat and dog owners, we investigated ectoparasiticide usage and the frequency of activities that are likely to result in transfer of the active substance to the environment, with a focus on pathways to waterways. A total of 603 dog owners and 406 cat owners completed the survey. Amongst dog and cat owners, 86.1% and 91.1% had administered an ectoparasiticide treatment to their pet in the preceding 12 months. Imidacloprid was the most frequently administered ectoparasiticide in both cats and dogs, followed by fluralaner in dogs and fipronil in cats. Eighty-four percent of owners who applied topical ectoparasiticides to their dog said they were aware of product warnings regarding swimming and bathing after application. Spot-on treated dogs were reported to swim significantly less frequently than non spot-on treated dogs (p = 0.007); however, 36.2% were reported to swim at least monthly. Similarly, significant differences were found in bathing frequency between spot-on treated and non spot-on treated dogs, with treated dogs less likely to be bathed at frequent (weekly) intervals, however 54.6% were reported to be bathed at least monthly. Washing of bedding was unaffected by ectoparasiticide treatment, and 87.8% of dog owners and 69.1% of cat-owners reported washing their pet’s bedding at least every 3 months, suggesting that residue washoff from bedding may be occurring for most topically treated animals. Results suggest that transfer of ectoparasiticides to the environment is likely to occur for many of the millions of animals treated annually in the UK, with imidacloprid spot-on treated dogs estimated to swim, be bathed and have their bedding washed over 3.3 million, 5 million and 6.3 million times per year, respectively.
Keywords: Parasiticides; Emissions pathways; Companion animals; Pet owner survey; Environmental pollution